Online shopping convenience and the level of used imported clothing consumption: The moderating role of hedonic and utilitarian traits - Fuad Qomaruddin Akbar; Ihwan Susila (Sebelas Maret Business Review, 2023)
Online shopping convenience has provided a separate impact on consumers who want to shop, making them feel facilitated by online shopping features. Online shopping convenience also impacts the sales of used imported clothing or what is more commonly known as thrifting. They consider it no problem to buy used imported clothing because of its low price and still wearable, even seeking clothing with well-known brands. Purchasing used imported clothing, commonly known as thrifting, is influenced by the ease of online shopping and hedonic and utilitarian attributes. This research was conducted to determine the effect of the convenience of online shopping on the level of consumption of imported used clothing in Central Java, which is moderated by hedonic and utilitarian traits. This quantitative study uses a non-probability sampling technique in the form of primary data obtained from questionnaire data distributed online in the form of a Google Form. This research produced 100 respondents with the criteria of buying used imported clothes online. The results of the study concluded that the convenience of online shopping had a positive and significant effect on the level of consumption of imported used clothing. The influence of 2 moderating variables in the form of hedonic and utilitarian characteristics results in the ease of online shopping, which is moderated by hedonic characteristics, and does not significantly affect the level of consumption of imported used clothing. Meanwhile, the ease of online shopping, moderated by utilitarian characteristics, negatively affects the consumption of imported used clothing.